2010
DOI: 10.2174/138955710791572433
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-Organic G-Quadruplex Ligands in Anticancer Drug Design

Abstract: Guanine-rich DNA sequences can form planar four-stranded structures via Hoogsteen hydrogen bonds. These sequences in telomeric DNA and some oncogenes have been identified as targets for novel anticancer drugs. Consequently, there is great current interest in developing small molecules that can facilitate the formation of, and stabilize G-quadruplexes as potent antitumor chemotherapeutic agents. Metal complexes with planar geometries and phi-delocalised ligands are emerging as a new class of quadruplex DNA liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In particular, some of them have recently received much attention for their ability to target DNA secondary structures known as Gquadruplexes. [1] G-quadruplex (G4) structures derive from the pairing of four guanines into planar arrangements (G-tetrads) that stack on each other. [2] The additional presence of cations, commonly Na + or K + ions, in the central cavity provides these highly stable tetrahelical structures.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, some of them have recently received much attention for their ability to target DNA secondary structures known as Gquadruplexes. [1] G-quadruplex (G4) structures derive from the pairing of four guanines into planar arrangements (G-tetrads) that stack on each other. [2] The additional presence of cations, commonly Na + or K + ions, in the central cavity provides these highly stable tetrahelical structures.…”
Section: Introductionmentioning
confidence: 99%
“…). Crystal structures revealed that Ni(II) complexes 55-64 and 73-82, Cu(II) complex 65 and Pt(II) complexes 68-72 have a planar geometry,[68][69][70][71] whereas the pentacoordinated V(IV)vO complex 67 has a quasi-planar geometry69,72 and the Zn(II)(H 2 O) complex 66 is non-planar 69. According to FRET, FID and SPR assays, all these planar metal-salphen complexes are effective G4 stabilizers whereas non-planar metal-salphen complexes only show low G4 affinity or specificity.…”
mentioning
confidence: 99%
“…These planar compounds wereFig. 8Metallosalphens with various side arms reported as G4-ligands [66][67][68][69][70][71][72][73]. Open Access Article.…”
mentioning
confidence: 99%
“…[8,9,36,37] G-quadruplex formation has been linked to telomer formation and has implications in cancer biology and ageing, and the stabilization of quadruplexes has the potential to control gene expression. [8,9,11] Schematic of formation of a dynamic combinatorial library formed from thiol and disulfide building blocks and detection of amplified products in the presence of a nucleic acid target using (a) biotinylated probes and streptavidin beads; [25,26] and (b) resin-bound dynamic combinatorial chemistry. [27] 3.…”
Section: Quadruplex Dnamentioning
confidence: 99%
“…[4,5] The study of small molecules that recognize and bind with high affinity and selectivity to duplex, triplex, and quadruplex DNA, as well as hairpins, bulges, and RNA loops has attracted significant interest because of the involvement of many of these structures in disease. [5][6][7][8][9][10][11] Medicinal and synthetic chemists have incorporated the features present in natural products to design new ligands in order to elucidate the rules that govern nucleic acid recognition. [5,12,13] While significant progress has been made in the design of synthetic molecules that bind to the minor groove of DNA, [12] the design of sequence-specific compounds that bind to the major or minor grooves remains challenging.…”
Section: Introductionmentioning
confidence: 99%